Psychosocial risks and work-related stress in developing countries: a call for research and action in policy development - Kortum, Evelyn (2011)
This research explores the understanding of psychosocial risks and work-related stress by international multi-disciplinary experts in developing countries. It further explores their views on the perceived health impact of these issues. It identifies preliminary priorities for action while considering similarities and differences in conceptualizing these issues in industrialized and developing countries. Finally, it explores in what ways these issues can enter the policy agenda in developing countries.